The Influence of Workload and Organizational Culture on Teachers’ Work Stress Levels - Hidayatullah, Nurfitri; Gistituati, Nurhizrah; Yahya; Alkadri, Hanif (Indonesian Research Journal in Education |IRJE|, 2024)
This research aims to reveal the influence of workload and organizational culture on the work stress level of State Middle School teachers in South Solok Regency. The population in this study was 502 teachers at all-state junior high school teachers in South Solok Regency. The research sample consisted of 87 teachers using the cluster random sampling technique. The research instruments used are assessment scales and Likert scale model questionnaires, which have been tested for validity and reliability. Research data was analyzed using correlation and regression techniques. The results of data analysis show that workload influences teacher work stress levels by 12.1%, organizational culture influences teacher work stress levels by 22.2%, and workload and organizational culture jointly affect teachers’ work stress levels by 32.6%. The achievement level for teacher work stress levels was 72.6% in the medium category. For workload, 71.60% was in the moderately burdened category, while for organizational culture, 74.71% of the ideal score was in the medium category.